Authority of the Investigation Supervision Division in Case Resolution at Bali Police - Sihotang, Erikson; Wiranti Rendang, Dewa Ayu Sinta; Suryana , Kadek Dedy (Al-Makki Publisher, 2025)
This research is entitled